Pengaruh Model Pembelajaran Course Review Horay Terhadap Kemampuan Komunikasi Matematik dan Kerjasama Siswa - Soffa Ma'arijah Nurhamidah; Eko Fajar Suryaningrat; Dea Asri Pujiasti (Bale Aksara: Jurnal Pendidikan Sekolah Dasar, 2022)
The focus of this research seeks to find: (1) the effect of the course review horay learning model on students' mathematical communication skills; (2) the effect of the course review horay learning model on student cooperation; and (3) the effect of the course review horay learning model on students' mathematical communication and collaboration skills. This study uses a quantitative approach with a quasi-experimental method where the subjects are third grade students at SDN 3 Sukaratu. Based on the results of the study, it was concluded that (1) there was an effect of the course review horay learning model on students' mathematical communication skills; (2) there is no effect of the course review horay learning model on student cooperation; and (3) there is an effect of the course review horay learning model on students' mathematical communication skills and collaboration